Pendidikan Pancasila dan Ketahanan Informasi di Era Post-Truth - Amir, Rafi'ul; Putri, Adinda Rizal; Zaini, Sindi Nur; Batubara, Taslim (Polyscopia, 2025)
The post-truth era, marked by the rampant spread of misinformation and hoakses in digital spaces, poses significant challenges for fostering critical information resilience among university students in Indonesia. This research analyzes the role of Civic and Pancasila Education (PPKn) in equipping students with information literacy skills. Utilizing a qualitative descriptive approach, data were collected through literature reviews and in-depth interviews with PPKn lecturers and students from multiple universities. The findings emphasize the effectiveness of integrating digital technologies, case-based learning, and simulations of information management into the PPKn curriculum. The study concludes that PPKn plays a dual role as a medium for internalizing Pancasila values and a strategic tool for fostering critical literacy skills among students in the digital age.